Are we overcoming our inability to have pediatric patients properly use inhaled corticosteroids by inappropriately escalating their therapy? (2021)
Objective To perform a narrative review to describe and discuss potential methods and strategies for effectively assessing and dealing with poor adherence and/or misuse of inhalers in difficult-to-treat pediatric asthmatic patients. Data sources Articles available in electronic databases, published from inception to April 2021. Study selections Relevant articles in the literature that discuss and analyze potential methods and strategies for effectively assessing and dealing with poor adherence and/or misuse of inhalers in difficult-to-treat pediatric asthmatic patients. Results Validated self-reported questionnaires, weighing inhaler canisters, and pharmacy records might be the most suitable methods for assessing adherence to inhaled controller therapy in clinical practice. Additionally, validated instruments could be used as an objective measurement of the adequacy of inhaler technique. Finally, empathy and a true and strong physician-parent/patient partnership have a more powerful influence on adherence than almost any other factor, and they are probably the most cost-effective methods not only for detecting poor adherence to controller therapy but also for dealing with and improving it. Conclusions Failure to detect or effectively handle nonadherence and/or inhaler misuse in a patient with uncontrolled asthma can mislead clinicians into thinking that the patient is nonresponsive to the original less-intensive therapy, resulting in unneeded dosage increases and/or escalation of controller therapy to more costly medications, in some cases reaching the level of biologic therapy.